Factors associated with delayed ambulance response time in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan - Di, Teo Sin (2018)
Ambulance response time is the key performance for ambulances services. The objective of this study is to determine the factors associated with delayed ambulance response time in Hospital Universiti Sains Malaysia. This was a cross sectional study conducted in Emergency Department Hospital Universiti Sains Malaysia between January 2016 to January 2017. A total of 300 samples had been collected by ambulance paramedic using validated ambulance form ‘Borang Sela Masa Tindak Balas Ambulans’. All ambulance forms with missing data were excluded in this study. Of 300 cases of emergency ambulance call cases, there were 254 cases (84.7%) of delayed ambulance response time. Current ambulance response time is 14 minutes with interquartile range of 5 minutes. Factors which showed significant association delayed ambulance response time include distance, location type and ambulance mechanism. The odd of delayed ambulance response time by every increase in distance unit was 1.59 (95% CI, 1.37 to 1.85). For location type, the odd of delayed ambulance response time for public location as compared to road was 0.13 (95% CI, 0.04 to 0.45). For ambulance mechanism, the odd of delayed ambulance response time for beacon type as compared to siren type was 0.22 (95% CI, 0.01 to 0.69). Distance, location type and ambulance mechanism showed significant association with delayed ambulance response time. Further intervention should be derived to improve current ambulance response time.